Building Information Modeling data interoperability for Cloud-based collaboration: Limitations and opportunities. (September 2017) - Afsari, Kereshmeh; Eastman, Charles; Shelden, Dennis
Collaboration within Building Information Modeling process is mainly based on the manual transfer of document files in either vendor-specific formats or neutral format using Industry Foundation Classes. However, since the web enables Cloud-based Building Information Modeling services, it provides an opportunity to exchange data with web technologies. Alternative data sharing solutions include the federation of Building Information Modeling models and an interchange hub for data exchange in real time. These solutions face several challenges, are vendor locked, and integrate Building Information Modeling applications to a third new system. The main objective of this article is to investigate current limitations as well as opportunities of Cloud interoperability to outline a framework for a loosely coupled network-based Building Information Modeling data interoperability. This study explains that Cloud-Building Information Modeling data exchange needs to deploy major components of Cloud interoperability such as Cloud application programming interfaces, data transfer protocols, data formats, and standardization to redefine Building Information Modeling data flow in Cloud-based applications and to reshape collaboration process.